2009
DOI: 10.1080/10691898.2009.11889525
|View full text |Cite
|
Sign up to set email alerts
|

Statistics? You Must be Joking: The Application and Evaluation of Humor when Teaching Statistics

Abstract: Humor has been promoted as a teaching tool that enhances student engagement and learning. The present report traces the pathway from research to practice by reflecting upon various ways to incorporate humor into the face-to-face teaching of statistics. The use of humor in an introductory university statistics course was evaluated via interviews conducted with a random sample of 38 students. Responses indicated that humor aided teaching by providing amusement, breaking up content, bringing back attention, light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Neumann, Hood, and Neumann (2009) found humour to be effective for students who held previous negative attitudes towards statistics, but for those who already were motivated and engaged in statistics, the humour was seen as distracting and irrelevant at times. However, other researchers have found that making statistics fun, through humour, cartoons, or songs, can be an effective teaching tool (Lesser & Pearl, 2008).…”
Section: Techniques For Teaching Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neumann, Hood, and Neumann (2009) found humour to be effective for students who held previous negative attitudes towards statistics, but for those who already were motivated and engaged in statistics, the humour was seen as distracting and irrelevant at times. However, other researchers have found that making statistics fun, through humour, cartoons, or songs, can be an effective teaching tool (Lesser & Pearl, 2008).…”
Section: Techniques For Teaching Statisticsmentioning
confidence: 99%
“…For instance, one technique involves the introduction of humour into the classroom as a strategy to enhance student engagement and learning (Neumann, Hood, & Neumann, 2009). Neumann, Hood, and Neumann (2009) found humour to be effective for students who held previous negative attitudes towards statistics, but for those who already were motivated and engaged in statistics, the humour was seen as distracting and irrelevant at times.…”
Section: Techniques For Teaching Statisticsmentioning
confidence: 99%
“…Research demonstrates that with humor, students learn better and remember more; and absorb information more quickly and retain it longer (e.g., Bryant & Zillman,1989;Opplinger, 2003;Schmidt, 2002). Furthermore, humor can aid teaching by providing amusement, breaking up content, bringing back attention, lightening the mood, increasing motivation, reducing monotony, and providing a mental break (Neumann, Hood, & Neumann, 2009). Humor increases students' enjoyment of learning, perceptions of how much they learned and positive feelings about the course and instructor (Wanzer & Frymier, 1999).…”
Section: How About Humor?mentioning
confidence: 99%
“…An emerging body of research suggests that certain types of fun items can be effective in improving statistics student attitudes and reducing student anxiety while increasing student interest, recall of material, and conceptual understanding (Berk 2009b;Berk & Nanda 1998Field 2010;Friedman, et al 2002;Garner 2006;Lomax & Moosavi 2002;Neumann, et al 2009). Other motivations from the literature reviewed by Lesser and Pearl (2008) include: building classroom community, reducing anxiety, humanizing the subject/instructor/course, fostering openness in the classroom, increasing students' attention and participation for the entire class period, providing a means of illustrating difficult concepts, and giving students a highly memorable way to recall specific content that will last well beyond the final exam (Friedman, et al 2002;Schacht & Stewart 1990).…”
Section: Motivationsmentioning
confidence: 99%
“…Lesser and Pearl (2008) provide a comprehensive overview of using fun in the statistics classroom, and the paper includes a table listing 20 modalities (with references or points of departure for each), implementation tips and some emerging evidence on potential effectiveness of some modalities. The accumulation of evidence is most established for the modality of humor and experimental studies of the pedagogical impacts of humor have shown significant positive outcomes in student ratings of the lesson, student ratings of the instructor, student anxiety, student attitudes towards statistics, and student recall and retention of information (Berk & Nanda 1998Garner 2006;Neumann, Hood & Neumann 2009). It is noted that the research on humor in the context of statistics is relatively recent in the overall four decades' worth of research on humor in educational settings (e.g., Banas, Dunbar, Rodriguez & Liu 2011).…”
Section: Introductionmentioning
confidence: 99%